2010
DOI: 10.1590/s0103-51502010000100009
|View full text |Cite
|
Sign up to set email alerts
|

Alterações fisiológicas e metabólicas em indivíduo com distrofia muscular de Duchenne durante tratamento fisioterapêutico: um estudo de caso

Abstract: INTRODUÇÃO: A Distrofia Muscular de Duchenne (DMD) caracteriza-se por uma perda progressiva da força muscular. O tratamento fisioterapêutico tem fundamental importância na manutenção da qualidade de vida desses pacientes. Contudo, existe grande dificuldade em graduar o grau de cansaço e o limite de exigência da musculatura durante o tratamento. Adicionalmente, não existe na literatura descrição sobre alterações fisiológicas e metabólicas durante uma atividade de esforço nessa população específica. OBJETIVOS: O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
4
0
4
Order By: Relevance
“…The same occurred with the diaphragm muscle, where the mdx animals showed signi cantly higher lipid peroxidation levels when compared to the non-exercised mdx animals, demonstrating that the exercise protocol for four weeks was able to prevent the increase in lipid peroxidation. However, swimming was not able to reverse the increase in protein carbonation in diaphragm [4]. Considering what was exposed, it can be suggested that moderate intensity aerobic exercise -swimming -can reduce oxidative stress by increasing antioxidant defenses such as the glutathione, considering the increase in the formation of free thiols shown in the results of this study.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The same occurred with the diaphragm muscle, where the mdx animals showed signi cantly higher lipid peroxidation levels when compared to the non-exercised mdx animals, demonstrating that the exercise protocol for four weeks was able to prevent the increase in lipid peroxidation. However, swimming was not able to reverse the increase in protein carbonation in diaphragm [4]. Considering what was exposed, it can be suggested that moderate intensity aerobic exercise -swimming -can reduce oxidative stress by increasing antioxidant defenses such as the glutathione, considering the increase in the formation of free thiols shown in the results of this study.…”
Section: Discussionmentioning
confidence: 52%
“…Evidence suggests that oxidative stress is associated with the aggravation of both respiratory and muscular pathology in these patients [19]. In addition, there are studies that show that exercise can protect against oxidative stress in skeletal muscle in mdx mice [4,13]. The protocol used in this study protected against the increase in lipid peroxidation in gastrocnemius in mdx animals.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As crianças realizaram o teste de caminhada na piscina em uma área denominada platô (superfície plana onde e realizado o treino de marcha) e percorreram uma distancia de 15 metros durante 06 minutos, foi oferecido o mesmo comando verbal do solo. Foi realizado primeiro o teste em solo e em seguida as crianças foram orientadas a manter o repouso de 30 minutos com objetivo de retornar os parâmetros basais e eliminar o fator fadiga 9,12,13 . Após este período foi realizado o teste no ambiente aquático.…”
Section: Procedimentounclassified
“…Treatment of patients diagnosed with Duchenne muscular dystrophy (DMD) needs to be multidisciplinary, careful, and always focused on the well-being of the patient. Given this, the role of physical therapy becomes crucial to the success of treatment, as it has achieved good results in the short term, such as maintenance of the autonomy of these individuals [4,5]. Another method that has been used to treat DMD is physical exercise [6,7].…”
Section: Introductionmentioning
confidence: 99%